If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + 20 = 3(y + 4) Reorder the terms: 20 + 5y = 3(y + 4) Reorder the terms: 20 + 5y = 3(4 + y) 20 + 5y = (4 * 3 + y * 3) 20 + 5y = (12 + 3y) Solving 20 + 5y = 12 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. 20 + 5y + -3y = 12 + 3y + -3y Combine like terms: 5y + -3y = 2y 20 + 2y = 12 + 3y + -3y Combine like terms: 3y + -3y = 0 20 + 2y = 12 + 0 20 + 2y = 12 Add '-20' to each side of the equation. 20 + -20 + 2y = 12 + -20 Combine like terms: 20 + -20 = 0 0 + 2y = 12 + -20 2y = 12 + -20 Combine like terms: 12 + -20 = -8 2y = -8 Divide each side by '2'. y = -4 Simplifying y = -4
| 4-7(2-5n)=-115 | | 0=8x^2-72 | | 12x=21 | | -29+x-6x=31 | | -c=x^2-24-y | | 144-3X^2=0 | | lnx=2+lny | | -43-5x-x=11 | | 7y-28/6y-24 | | y=x^2-24+c | | -9x-104-4x=91 | | 0=X^2+76 | | T/6/-3 | | -67+2x+9x=54 | | 66+24= | | (3x^3-16x^2+12x+16)/(x+1) | | 8x-112+6x=70 | | 23x+7-25x=4-5 | | z=16 | | 2*33+24= | | -x+3x-18=20 | | -4y+6=-5y+5 | | 2x+24=90 | | -9x-65+4x=30 | | 9x+14-8x=-4-12 | | -2x-33-3x=57 | | 3000-30*68= | | -141+3x+6x=39 | | 3000-30P= | | 3x-2(-x+4)=x+32 | | -5x-60-x=36 | | -400+20*68= |